(untitled) (International Journal of Engineering and Computer Science, 2014)
In recent years, image and video encoding has become more popular in network access. The rapid development in wired and wireless digital communication has made the extensive use of the text data. However, there are few researches focusing on encoding data and memory usage. The basic characteristics of text data like transmission rate, bandwidth, redundancy, bulk capacity and co-relation among text data makes basic compression algorithms mandatory. Therefore this paper considers the problem of memory usage and encoding scheme to provide low bit rate transmission based on HUFFMAN coding. As for n bit being transmitted it requires 2n memory stack for further increase in the data bits it requires 2n+1 memory stack which is wide waste of memory if there presents redundancy bits. Image transmission has large repeated sequences at some places which can be considered as redundant. The proposed method uses stuffing bits in order to provide high speed and low cost transmission